Sungai Muar Monitoring System for Seawater Intrusion - Theevaarasan,; Mohd Shamian Zainal, (Progress in Engineering Application and Technology, 2024)
This project aims to create an automated water quality monitoring system with a conductivity sensor and GSM module to combat seawater intrusion in Sungai Muar. By monitoring the river's salinity levels continuously, the system offers real-time data to identify high salinity, indicating possible contamination. The project emphasises incorporating modern technology like I2C communication, Modbus RTU protocol, and SoftwareSerial for efficient data processing and communication. Successful tests affirm the sensor's precision and the GSM module's ability to send timely SMS alerts to relevant authorities. The collected data can be utilised to compare ideal conductivity ranges for various plants and animals, aiding in effective water management to support growth, health, and productivity while reducing the adverse effects of seawater intrusion. The performance analysis of the water monitoring system in detecting Sungai Muar's conductivity level was successful, as the prototype consistently delivered precise and reliable data with an accuracy rate of 98% during testing. The system showed high accuracy in detecting conductivity fluctuations, meeting initial objectives, and delivering expected results. The system's architecture and circuit layout were meticulously planned, and the prototype effectively measured Sungai Muar's conductivity and salinity levels, showcasing its capacity to offer accurate and reliable data, confirming its practical usability, and achieving all primary goals.